1976
DOI: 10.4039/ent108893-8
|View full text |Cite
|
Sign up to set email alerts
|

TRANSLOCATION OF CACODYLIC ACID IN DUTCH ELM-DISEASED AMERICAN ELMS AND ITS EFFECT ON SCOLYTUS MULTISTRIATUS (COLEOPTERA: SCOLYTIDAE)

Abstract: Can. Ent. 108: 893-896 (1976) Cacodylic acid was injected into hatchet-made frill girdles 60 cm above the ground on Dutch elm-diseased American elms (Ulmus americana L.) at the rate of 0.8 ml/cm circumference measured 1.3 m above the ground. Cacodylic acid was translocated up the trees into the phloem. Arsenic residue analyses at several different heights in each tree indicated an inverse relationship between height and amount of cacodylic acid residue in the phloem. Largest amounts were translocated in tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…However, arsenic levels in foliage from MSMA-treated lodgepole pine trees, Pinus contorta var. Hostetler and Brewer (1976) determined that arsenic levels in the phloem of untreated diseased elms in Colorado ranged from 1 to 14 ppm and in cacodylic acid-treated diseased elms from 13 to 506 ppm, with arsenic levels decreasing sharply with height. In addition, arsenic was relatively tightly bound in foliage and did not move rapidly from the forest litter to the underlying soil (Norris et al 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, arsenic levels in foliage from MSMA-treated lodgepole pine trees, Pinus contorta var. Hostetler and Brewer (1976) determined that arsenic levels in the phloem of untreated diseased elms in Colorado ranged from 1 to 14 ppm and in cacodylic acid-treated diseased elms from 13 to 506 ppm, with arsenic levels decreasing sharply with height. In addition, arsenic was relatively tightly bound in foliage and did not move rapidly from the forest litter to the underlying soil (Norris et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Our study was conducted on healthy, non-diseased elms; however, herbicide treatments can be applied to elms with varying degrees of Dutch elm disease (Himelick and Neely 1961;Lanier 1982;Hostetler and Brewer 1976;Rexrode 1974). Herbicide application on elms with advanced symptoms showed the greatest variability in efficacy, because the fungus plugs the phloem vessels, inhibiting herbicide penetration (Himelick and Neely 1961).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, arsenic was relatively tightly bound in foliage and did not move rapidly from the forest litter to the underlying soil (Norris et al 1983). Hostetler and Brewer (1976) determined that arsenic levels in the phloem of untreated diseased elms in Colorado ranged from 1 to 14 ppm and in cacodylic acid-treated diseased elms from 13 to 506 ppm, with arsenic levels decreasing sharply with height.…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of failed broods in conifers killed in thinning operations, several studies showed that cacodylic acid and MSMA could be useful for control of bark beetles (5,2,7,6). Rexrode (22) reported 100% mortality of elm bark beetle broods in small elms pressure-injected with cacodylic acid, but Hostleter and Brewer (10) found no significant mortality of European elm bark beetles in diseased trees topically treated with cacodylic acid in Colorado. (The timing of the treatment (August) and examination for emergence (December) indicates that the infestation was already established when trees were treated.)…”
mentioning
confidence: 99%